A dual-responsive artificial skin for tactile and touchless interfaces - Wang, Hai Lu (2023)
The progress from intelligent interactions and supplemented/augmented reality requires artificial skins to shift from the single-functional tactile paradigm. Dual-responsive sensors that can both detect pre-contact proximal events and tactile pressure levels enrich the perception dimensions and deliver additional cognitive information. Previous dual-responsive sensors show very limited utilizations only in proximity perception or approaching switches. Whereas, the approaching inputs from the environment should be able to convey more valuable messages. Herein, a flexible iontronic dual-responsive artificial skin is present. The artificial skin is sensitive to external object's applied pressure as well as its approaching, and can elicit information of target material categories encoded in the proximal inputs. Versatile applications are then demonstrated. Dual-mode human-machine interfaces are developed based on the devices, including a manipulation of virtual game characters, navigation and zooming in of electronic maps, and scrolling through electronic documents. More importantly, the proof-of-concept application of an entirely touchless material classification system is demonstrated. Three types of materials (metals, polymers, and human skins) are classified and predicted accurately. These features of the artificial skin make it highly promising for next-generation smart engineered electronics.